Politeness Strategies in Jimmy Kimmel Live with David Beckham’s Guest Appearance on Youtube (Sastra Inggris UNPAM, 2024)
This study aims to identify any kinds of politeness strategies, understand how talk shows influence people's perceptions of important issues and how they shape public culture through mass media used in Jimmy Kimmel Live with David Beckham’s Guest Appearance on Youtube. The writer uses a descriptive qualitative method to explain the data and follows the theory of Brown and Levinson (1987) to answer the statement of the problem. Besides on the finding, the writers found the conversation on Jimmy Kimmel Live with David Beckham on Youtube reveals 149 politeness strategies, with positive politeness being the most common, appearing 107 times. Then, 11 bald on record, 18 negative politeness, and 13 off record. Additionally, the results show that 149 different politeness techniques were employed during Jimmy Kimmel and David Beckham's interaction. It can be concluded that politeness strategy is one of the things that are very important for interactions to respect and maintain the self-esteem of others. The implications study shed light on the practical purposes of manners and their influence on discourse and social interactions. The examination of politeness strategies in this particular setting advances our knowledge of interpersonal communication dynamics and the methods speakers use to successfully negotiate social norms and accomplish communication objectives.